(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Food fraud is one of the risks in the supply chain globalization. A complex and long supply chain with different locations, cultures, business ethics, policies and surveillance systems are the contributing factors to food fraud. This study aims to identify food fraud vulnerability factors in milk powder producers. It was conducted in two companies which uses powder and liquid milk as the raw materials which is typical in Indonesian powdered milk industry. The study steps consist of respondents determination, data collection and analysis, formulating mitigation strategies. The respondents were company’s head of departments and a government officer of the National Agency for Drug and Food. Data collection and analysis were carried out with the Safe Supply Affordable Food Everywhere (SSAFE) tool, while mitigation strategies was formulated through Focus Group Discussion. The results show that vulnerability to food fraud rooted from the opportunity factor, namely the easiness and availability of technology to commit fraud, motivational factor namely the level of corruption and regulatory differences that affect prices, control measures factors due to lack of supervision, employee integrity tests and prevention guidelines. Internally improving control measures within the company and guideline prevention from the government were mitigation measures to be done.